Sequencing of nucleic acids - Furlani, Borut (Acta chimica slovenica, 2021)
Despite being around for more than 40 years, DNA sequencing is regarded as young technology in clinical medicine. As sequencing is becoming cheaper, faster and more accurate, it is rapidly being incorporated into clinical laboratories. In 2003, the completion of the first human genome opened the door to personalized medicine. Ever since it has been expected for genomics to widely impact clinical care and public health. However, many years can pass for genomic dis-coveries to reflect back and benefit the patients. DNA sequencing represents a less biased approach to diagnostics. It is not only a diagnostic tool, but can also influence clinical management and therapy. As new technologies rapidly emerge it is important for researchers and health professionals to have basic knowledge about the capabilities and drawbacks of the existing sequencing methods, and their use in clinical setting and research. This review provides an overview of nucleic acid sequencing technologies from historical perspective and later focuses on clinical utilization of sequencing. Some of the most promising areas are presented with selected examples from Slovenian researchers.
Keywords: clinical sequencing; genomics; genomika; klinično zaporedje; nucleic acid; nukleinska kislina